Hubungan antara Resolusi Konflik dengan Kepuasan Pernikahan pada Remaja Menikah Dini - Rina Oktaviana; Piraini Piraini (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This study aims to determine the relationship between conflict resolution and marital satisfaction in early married adolescents. This research design uses quantitative research. The research instrument used is the Conflict Resolution Scale and the Marriage Satisfaction Scale. The subjects involved in this study amounted to 161 early married couples who were obtained using purposive sampling technique. The data obtained were then analyzed using simple regression, namely, to make an estimate of the value of the variables. This study shows that there is a significant relationship between conflict resolution and marital satisfaction in Adolescent couples married early in Talang Jaya Village (p0.001; R Square 0.251).